Effect of combined colloid preloading and crystalloid coloading versus combined colloid and crystalloid coloading on maternal cardiac output during spinal anesthesia for cesarean section under combined prophylactic noradrenaline infusion - Gao, Xiang; Huang, Yu; Hu, Sumei; Lin, Chuantao; You, Yi; Huang, Shihong; Liu, Ming; Yan, Jianying (Frontiers in Medicine, 2025)
ObjectiveHypotension is a common complication of spinal anesthesia during cesarean section, and no single intervention has been shown to eliminate maternal hypotension. Fluid loading strategies combined with vasopressor drug regimens can achieve this goal by maximizing cardiac output (CO) and minimizing the fall in systemic vascular resistance (SVR). However, the optimal fluid volume, type, and timing of administration have not been fully elucidated. Therefore, this study aimed to use Vigileo techniques in order to compare the effects of different fluid loading strategies on CO fluctuation under a norepinephrine infusion.MethodsWe recruited 102 healthy term parturients scheduled for elective cesarean section under spinal anesthesia for this randomized double-blind study and divided them into two groups: the colloid preload followed by crystalloid coload group (500 ml each; Group 1, n = 51), and the colloid and crystalloid coload group (500 ml each; Group 2, n = 51). The infusion of norepinephrine was started after intrathecal injection. Vigileo was used to monitor invasive hemodynamic indices. Our primary outcome was standardized maternal cardiac output (CO) readings taken from spinal anesthesia until delivery. The secondary outcome measures were stroke volume (SV), systolic blood pressure (SBP), heart rate (HR), number of episodes of hypotension, hypertension, bradycardia, nausea/vomiting and total norepinephrine dose. Neonatal outcome was assessed by recording Apgar scores 1 and 5 min after delivery and by measuring umbilical arterial (UA) blood gases. Continuous hemodynamic monitoring was performed during the first 15 min after spinal anesthesia.ResultsBaseline CO, SV, and SBP were similar for both groups. Before spinal anesthesia, CO (6.84 ± 1.18 vs. 5.51 ± 0.96 L/min, P < 0.001) was significantly higher in group 1 than group 2, but this increase was not sustained after spinal anesthesia (P > 0.05). SV (75.98 ± 13.01 vs. 66.37 ± 12.42 mL, P < 0.001) and SBP (124.84 ± 11.61 vs. 116.57 ± 7.57 mmHg, P < 0.001); followed a similar trend in the study. Only the largest percentage change in maternal HR (4.89 ± 11.89 vs. 10.38 ± 14.07, P = 0.036) was significantly different between the two groups. There were no significant differences between the two groups in terms of the maximum CO, SV, SBP, or HR after spinal anesthesia (P > 0.05). The maternal side effects and neonatal outcomes, were similar in two groups (P > 0.05).ConclusionIn combination with prophylactic norepinephrine infusion, 500-mL colloid preloading and 500-mL crystalloid coloading can significantly increase CO before spinal anesthesia for cesarean sections and provide improved hemodynamic stability after spinal anesthesia, with no difference in maternal or neonatal outcomes as compared to colloid and crystalloid coloading.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2300073333.